2013
DOI: 10.1292/jvms.12-0208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Single Bolus Intravenous Dose of Tramadol on Minimum Alveolar Concentration (MAC) of Sevoflurane in Dogs

Abstract: ABSTRACT. Tramadol is an atypical opioid analgesic widely used in small animal practice. This study was designed to determine the effect of a single intravenous (IV) dose of tramadol on the minimum alveolar concentration (MAC) of sevoflurane in dogs. Six beagle dogs were anesthetized twice to determine the sevoflurane MAC with or without an administration of tramadol (4 mg/kg, IV) at 7 days interval. The sevoflurane MAC was determined using a tail clamp method in each dog ventilated with positive pressure vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 22 publications
(39 reference statements)
2
24
0
1
Order By: Relevance
“…The MAC reduction found in this study is similar to the one reported by Itami et al (2013), who obtained MAC reduction of 1.86 to 1.44 vol%, (approximately 22%) after the administration of tramadol in a single dose. In a study with rats (Wolff et al 1999), it was observed that tramadol could reduce the MAC of isoflurane.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The MAC reduction found in this study is similar to the one reported by Itami et al (2013), who obtained MAC reduction of 1.86 to 1.44 vol%, (approximately 22%) after the administration of tramadol in a single dose. In a study with rats (Wolff et al 1999), it was observed that tramadol could reduce the MAC of isoflurane.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have evaluated the effect of drugs combinations administered by continuous IV infusion on the requirement for inhalational agents. Studies with sevoflurane have obtained different basal MAC: 2.2-2.3 vol% (Matsubara et al 2009, Columbano et al 2012) and 1.82-1.9 vol% (Wilson et al 2008, Itami et al 2011, Itami et al 2013, Moran-Muñoz et al 2014. This variation may be due to methodological differences, since various stimuli can be applied, such as electrical stimulation, surgical incisions, digital pressure, tail clamping or movement of the endotracheal tube (Ebert & Schmid 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[45][46][47][48] Pharmacodynamic studies demonstrate the anesthestic-sparing and pain-modifying effect of parenteral tramadol in dogs. [49][50][51][52][53] Convincing evidence for a painmodifying effect of oral tramadol, however, remains elusive, and already low plasma levels quickly diminish with sequential administration. [54][55][56][57] one small study of oral tramadol did report a statistically significant increase of mechanical threshold levels in dogs, but only at the 5 and 6 h time points.…”
Section: Systemic Lidocainementioning
confidence: 99%